Exhaustion of CD8pos central memory regulatory T cell differentiation is involved in renal allograft rejection - Kälble, Florian; Leonhard, Jonas; Zeier, Martin; Zivanovic, Oliver; Schaier, Matthias; Steinborn, Andrea (Frontiers in Immunology, 2025)
BackgroundThe role of regulatory CD8pos T cells (CD8pos Tregs) and cytotoxic CD8pos responder T cells (CD8pos Tresps) in maintaining stable graft function in kidney transplant recipients (KTR) remains largely unclear. The pathogenesis of graft deterioration in case of rejection involves the exhaustive differentiation of both CD8pos T cell subsets, but the causal mechanisms have not yet been identified.MethodsIn this study, we separately investigated the differentiation of CD8posTregs/Tresps in 134 stable KTR with no evidence of renal graft rejection, in 41 KTR diagnosed with biopsy-confirmed rejection at enrolment and in 5 patients who were unremarkable at enrolment, but developed rejection within three years of enrolment. We were investigating whether changed differentiation of CCR7posCD45RAposCD31pos recent thymic emigrant (RTE) cells via CD45RAnegCD31pos memory (CD31pos memory) cells (pathway 1), via direct proliferation (pathway 2), or via CCR7posCD45RA+CD31neg resting mature naïve (MN) cells (pathway 3) into CD45RAnegCD31neg memory (CD31neg memory) cells affects the CD8pos Treg/Tresp ratio or identifies a CD8pos Treg/Tresp subset that predicts or confirms renal allograft rejection.ResultsWe found that RTE Treg differentiation via pathway 1 was age-independently increased in KTR, who developed graft rejection during the follow-up period, leading to abundant MN Treg and central memory Treg (CM Treg) production and favoring a strongly increased CD8pos Treg/Tresp ratio. In KTR with biopsy-confirmed rejection at the time of enrolment, an increased differentiation of RTE Tregs into CCR7negCD45RAposCD31neg terminally differentiated effector memory (CD31neg TEMRA Tregs) and CD31pos memory Tregs was observed. CD31neg memory Treg production was maintained by alternative differentiation of resting MN Tregs, resulting in increased effector memory Treg (EM Treg) production, while the CD8pos Treg/Treg ratio was unaffected. An altered differentiation of CD8pos Tresps was not observed, shifting the Treg/Tresp ratio in favor of Tregs.ConclusionsOur results show that exhaustive CD8pos Treg differentiation into CM Tregs may lead to future rejection, with a shift towards EM Treg production and an accumulation of CD31neg TEMRA Tregs in KTR with current rejection.